1996
DOI: 10.1021/bi9527294
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrrole Locus Is the Major Orienting Factor in Ryanodine Binding

Abstract: Ryanodine, a natural product, is a complex modulator of a class of intracellular Ca2+ release channels commonly called the ryanodine receptors. Ryanodine analogs can cause the channel to persist in long-lived, subconductance states or, at high ligand concentrations, in closed, nonconducting states. In this paper, we further explore the relationship between structure and ryanodine binding to striated muscle. Ryanodine, 3-epiryanodine, and 10-ryanodine are three structural isomers of ryanodine. The dissociation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…In the case of RyR2, which has Ϸ84 free SH residues (Ն360 cysteine residues total), oxidation of these groups will alter the activity of the channel (either increasing or decreasing activity). We and others have also shown that the pyrrole moiety is an essential determinant for ryanodine to bind to RyR1 (Welch et al, 1996;Bidasee and Besch, 1998). With these two pieces of information, we rationalized that a sulfhydryl reagent containing a pyrrole moiety might be useful to probe the oxidative state of cysteine residues in proximity to (or within) the vicinity of the ryanodine binding site(s) on RyR2.…”
Section: Synthesis Of 5h10h-dipyrrolo[12-a:12-d]pyrazine-510-dionmentioning
confidence: 80%
“…In the case of RyR2, which has Ϸ84 free SH residues (Ն360 cysteine residues total), oxidation of these groups will alter the activity of the channel (either increasing or decreasing activity). We and others have also shown that the pyrrole moiety is an essential determinant for ryanodine to bind to RyR1 (Welch et al, 1996;Bidasee and Besch, 1998). With these two pieces of information, we rationalized that a sulfhydryl reagent containing a pyrrole moiety might be useful to probe the oxidative state of cysteine residues in proximity to (or within) the vicinity of the ryanodine binding site(s) on RyR2.…”
Section: Synthesis Of 5h10h-dipyrrolo[12-a:12-d]pyrazine-510-dionmentioning
confidence: 80%
“…The binding site has been localized to the COOH-terminal region in the linear sequence in biochemical studies (18,19). Studies with ryanoids have predicted that pyrrole and isopropyl groups are embedded deep inside a cleft in RyR molecules (39).…”
Section: Discussionmentioning
confidence: 99%
“…2d, ©) would be only 3-fold less than that of ryanodine (OE) because a recent study proposed overwhelming dominance of the pyrrole for binding affinity (36). The present data (especially those on potency and efficacy, see below) suggest that the six-membered C 3 substituent of pyridyl ryanodine is accommodated almost equally well as the five-membered substituent of ryanodine.…”
Section: Relative Binding Affinities Of C 10 -O Eq Derivatives Of Thementioning
confidence: 48%